The Impact of Long-Term Care Home Ownership and Administration Type on All-Cause Mortality from March to April 2020 in Madrid, Spain - Maria Victoria Zunzunegui; Manuel Rico; François Béland; Fernando J. García-López (MDPI AG, 2022)
Our aim is to assess whether long-term care home (LTCH) ownership and administration type were associated with all-cause mortality in 470 LTCHs in the Community of Madrid (Spain) during March and April 2020, the first two months of the COVID-19 pandemic. There are eight categories of LTCH type, including various combinations of ownership type (for-profit, nonprofit, and public) and administration type (completely private, private with places rented by the public sector, administrative management by procurement, and completely public). Multilevel regression was used to examine the association between mortality and LTCH type, adjusting for LTCH size, the spread of the COVID-19 infection, and the referral hospital. There were 9468 deaths, a mortality rate of 18.3%. Public and private LTCHs had lower mortality than LTCHs under public-private partnership (PPP) agreements. In the fully adjusted model, mortality was 7.4% (95% CI, 3.1-11.7%) in totally public LTCHs compared with 21.9% (95% CI, 17.4-26.4%) in LTCHs which were publicly owned with administrative management by procurement. These results are a testimony to the fatal consequences that pre-pandemic public-private partnerships in long-term residential care led to during the first months of the COVID-19 pandemic in the Community of Madrid, Spain.